Measurement and influencing factors of urban waterfront street vitality from the perspectives of behavior and perception - Xiang Ji; Yao Fu; Jiaxuan Shi; Haixiao Liu (Environmental Research Communications)
Serving as the direct interface for interaction between the waterfront and urban dwellers, the street space environment significantly influences people’s living experiences and social interactions. Despite progress in the renovation and development of waterfront streets, these areas remain underutilized and lack the vitality expected of such locations. Using the Hunhe Waterfront Streets in Shenyang as a case study, this research employed Baidu heatmap data and the Semantic Differential method to assess both the behavioral and perceived vitality of the area. Subsequently, the study explored the main factors influencing behavioral vitality in waterfront streets from three aspects: street accessibility, facility configuration and environmental construction. It also examined the key environmental features of waterfront streets that affect perceived vitality under visual perception. Additionally, the study performed a coupling analysis to explore the relationship between behavioral and perceived vitality within the waterfront streets. The results indicated that the density of infrastructure and commercial facilities, as well as the continuity of pedestrian paths, were key environmental features influencing behavioral vitality. The degree of motorization, green visual index and building enclosure ratio were the main environmental features affecting perceived vitality. Moreover, the vitality coordination of the Hunhe Waterfront Streets was relatively poor, leaving considerable room for improvement. By integrating behavior and their perceptions of the environment, the study explored the coordination of waterfront street vitality and its intrinsic connection with street environmental features. This work aids in developing more effective and user-centric design strategies for waterfront streets, offering practical guidance for their revitalization and redevelopment.